2012
DOI: 10.1097/gme.0b013e318230e286
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of premenopausal and postmenopausal women with acquired, generalized hypoactive sexual desire disorder

Abstract: Most women with HSDD were in long-term partner relationships with high levels of overall relationship satisfaction. Postmenopausal women were more likely to seek help for their disorder, despite similarly high levels of distress associated with HSDD. Further research is needed to examine treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 24 publications
1
25
0
1
Order By: Relevance
“…In humans, the role of testosterone in female bone formation is still not well understood. As mentioned, it is clear that the majority of testosterone's effects in this decrease in testosterone has been implicated in postmenopausal decreases in libido, and possibly to hypoactive sexual desire disorder (HSDD), defined as a deficiency of sexual fantasies and desire for normal sexual activity that causes significant stress or interpersonal difficulty (89). In general, some studies suggest a correlation between serum testosterone levels and sexual desire (90, 91), but others do not (92,93).…”
Section: Androgen Action In Womenmentioning
confidence: 99%
“…In humans, the role of testosterone in female bone formation is still not well understood. As mentioned, it is clear that the majority of testosterone's effects in this decrease in testosterone has been implicated in postmenopausal decreases in libido, and possibly to hypoactive sexual desire disorder (HSDD), defined as a deficiency of sexual fantasies and desire for normal sexual activity that causes significant stress or interpersonal difficulty (89). In general, some studies suggest a correlation between serum testosterone levels and sexual desire (90, 91), but others do not (92,93).…”
Section: Androgen Action In Womenmentioning
confidence: 99%
“…A cross‐sectional, demographically representative U.S. population‐based survey conducted in 2006 found that approximately 1 in 10 premenopausal women reported low sexual desire with associated distress, which may indicate HSDD [2]. HSDD is believed to be the most common form of Female Sexual Dysfunction but remains underdiagnosed and undertreated [3–5].…”
Section: Introductionmentioning
confidence: 99%
“…In the Hypoactive Sexual Desire Disorder Registry for Women study, a large observational study of US women with clinically diagnosed generalized acquired HSDD, arousal disorders, lubrication problems, or both were reported by 50.2%, 42.5%, and 39% of women with HSDD, respectively. 48,49 A list of some potentially useful screeners and questionnaires is provided in the Supplemental Table (available online at http://www.mayo clinicproceedings.org).…”
Section: Modifiable Factorsmentioning
confidence: 99%